Development Aid, Remittances Inflows and Wages in the Manufacturing Sector of Recipient-Countries - Sèna Kimm Gnangnon (ZBW – Leibniz Information Centre for Economics, 2020)
This article has considered the effect of development aid and remittances inflows on wages in the manufacturing sector of the recipient-economies. The empirical analysis has used a sample of 95 countries over the period 1963-2016, and on the two-step system Generalized Methods of Moments (GMM). Results show for the full sample that while remittances influence positively wages, development aid exerts a negative effect on wages, although LDCs enjoy a positive effect of development aid on wages. Additionally, the effects of development aid and remittances on wages depend on the prevailing real exchange rate as well as the values of manufacturing exports.
Keywords: F35; J30; O14; 330; Development aid; Remittances inflows; Wages in the manufacturing sector; Real Exchange Rate; Manufactured exports